Effect of Flammulina velutipes on the physicochemical and sensory characteristics of Cantonese sausages. (August 2019) - Wang, Xuping; Xu, Mingying; Cheng, Jingrong; Zhang, Wei; Liu, Xueming; Zhou, Pengfei
Abstract: The effects of fresh and dried Flammulina velutipes (FFV and DFV) on quality and sensory characteristics of Cantonese sausages were investigated. Sausage samples were prepared by adding 0% (control), 2.5% FFV, 2.5% and 5.0% DFV, respectively, and their nutritional compositions, free amino acid profiles, lipid and protein oxidation, color and texture properties were determined. Addition of F. velutipes significantly decreased fat content while increased free amino acid contents of Cantonese sausages. Total free amino acid contents of 2.5% FFV, 2.5% DFV and 5.0% DFV incorporation were 2.8-, 2.4- and 3.5-fold as compared to control, respectively. Lipid and protein oxidation of Cantonese sausages were effectively inhibited by the addition of F. velutipes . Both FFV and DFV addition decreased hardness and chewiness while showed different effect on yellowness of samples. DFV added at 2.5% exhibited the best overall sensory acceptance. Therefore, appropriate addition of F. velutipes may be an effective way to improve meat product quality and function. Highlights: The quality and sensory characteristics of sausages can be improved by addition of F. velutipes . Addition of F. velutipes significantly decreased fat content of Cantonese sausages. Lipid and protein oxidation can be effectively inhibited by the addition of F. velutipes . Sausages incorporated with 2.5% dried F. velutipes showed the best overall sensory acceptance.